REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN STRATEGI PEMBELAJARAN REACT PADA MATERI KALOR DI SMPN 9 PONTIANAK - Siagawati, Yunita Dwi; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is a pre-experimental design of one group pretest posttest design to determine the effect of remediation using REACT learning strategies to remediating student’s misconceptions about the Heat. This was done by collecting quantitative data with two instruments, pretest to determine student misconception before remediation and posttest to determine student misconceptions after remediation. Data was collected by using the diagnostic test in the form of multiple-choice comprised of nine questions by representing three concepts related to Heat arrengged using Modified Certainty of Response Index (Modified CRI). The test was administered to 36 grade 7th students. It is found that the REACT learning strategies can affect student’s misconceptions about the Heat. The average percentage of the decreasing of number of student’s misconceptions each concept is 61% and the effect size of this study is 0,74. This research showed the REACT learning strategies can be used as an alternative remediation activities to reduce student’s misconceptions.Keyword : Remediation, Misconception, REACT Learning Strategies